Postmortem findings of malignant pleural mesothelioma: A two-center study of 318 patients - Finn, R.; Brims, Fraser; Gandhi, A.; Olsen, N.; Musk, A.; Maskell, N.; Lee, Y. (American College of Chest Physicians, 2012)
Background: Malignant pleural mesothelioma (MPM) is an incurable cancer with a rising incidence. MPM is often perceived as a locally invasive cancer, and the exact cause of death is poorly understood. This two-center study describes the anatomic features of patients with MPM at postmortem. Methods: The Western Australia Mesothelioma Registry (Australia) and Coroner's Office reports from the Avon region (England) were interrogated for the postmortem records of confirmed mesothelioma cases. Results: Postmortem records of 318 patients with pleural mesothelioma (169 from Western Australia and 149 from Avon) were identified. Most patients (91.5%) were men (mean age, 68.4 ± 11.5 years), and MPM was right-sided in 55.3%. Extrapleural dissemination of tumor was found in 87.7% of cases and lymph node involvement in 53.3%. Tumor dissemination in extrathoracic sites was common (55.4% of patients), and almost all organs were involved, including liver (31.9%), spleen (10.8%), thyroid (6.9%), and the brain (3.0%). Pulmonary emboli were found in 6% of cases and considered as directly contributing to death in 13 patients (4.1%). The precise cause of death could only be determined in 63 (19.8%) cases even after postmortem. The BMI was significantly lower in cases that had no identifiable anatomic cause of death at postmortem (18.8 ± 4.3 vs 21.0 ± 4.7, P = .034). Conclusions: In this largest, to our knowledge, postmortem series on MPM, extrathoracic dissemination of mesothelioma was common and often underrecognized. No anatomic cause of death was identified in the majority of patients even at autopsy, raising the possibility of physiologic and metabolic causes of death. © 2012 American College of Chest Physicians.